PENGARUH KOMITMEN PROFESIONAL DAN MOTIVASI TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MODERASI (STUDI PADA SMA NEGERI RAYON 2 DI KOTA SEMARANG) - Martadi, Damianus Nursih; Srimindarti, Ceacilia (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims (1) to test and analyze the effects of professional commitment to the teacher performance of teachers to the teacher of SMA Negeri Rayon 2 in the city of Semarang. (2) to examine and analyze the motivation against the teacher performance of teachers to the teacher of SMA Negeri Rayon 2 in the city of Semarang. (3) to test and analyze the organizational commitment moderates effect of the professional commitment to teacher performance of teachers of SMAN Rayon 2 in the city of Semarang. (4) to examine and analyze the organizational commitment moderate the effect of the professional commitment to the teacher performance of teachers of SMAN Rayon 2 in the city of Semarang. (5) to examine and analyze the organizational commitement moderates the motivation to the teacher performance of teachers of SMAN Rayon 2 in the city of Semarang. The population in this study were teachers of SMAN rayon 2 in the city of Semarang totaling 400 people. Samples are take using purposive sampling technique, They are 200 teachers. Mechanical analysis using multiple linear analysis model testing, test , hypothesis testing using t test and regression testmoderation. The results showed that; (1) professional commitment does not effect to the teacher performance; (2) motivation significant and positive impact of 71.9% to teacher performance; (3) Organization commitment significant and positive impact amounting to 46,6% of the teacher performance, (4) The organizational commitment does not moderate the influence of professional commitment to teacher performance; (5) An organizational commitment does not moderate the influence of motivation on teacher performance. Keywords: professional commitment, motivation, orgnizational commitment and teacher performance.